The sensitivity of Pseudomonas pseudomallei to trimethoprim and sulphamethoxazole in vitro - Bassett, D. C. J. (1971)
Twelve out of 14 strains of Pseudomonas pseudomallei were inhibited in vitro by a combination of trimethoprim 1 μg per ml and sulphamethoxazole 20 μg per ml or by lower concentrations. Of the remaining strains, one was marginally more resistant and one was distinctly so. In tests utilizing two of the sensitive strains, inhibitory concentrations of the individual drugs exerted a bactericidal effect when combined.